Corpus linguistics and its aplications in higher education - Fuster Márquez, Miguel; Clavel Arroitia, Begoña (Alicante Journal of English Studies / Revista Alicantina de Estudios Ingleses, 2010)
The aim of this paper is to review and analyse relevant factors related to the implementation of corpus linguistics (CL) in higher education. First we set out to describe underlying principles of CL and its developments in relation to theoretical linguistics and its applications in modern teaching practices. Then we attempt to establish how different types of corpora have contributed to the development of direct and indirect approaches in language teaching. We single out Data Driven Learning (DDL) due to its relevance in applied linguistics literature, and examine in detail advantages and drawbacks. Finally, we outline problems concerning the implementation of CL in the classroom since awareness of the limitations of CL is vital for its future success.